The development of brand awareness in young children: how do young children recognize brands?. (September 2016) - Aktaş Arnas, Yaşare; Taş͓, Işıl; Gürgah Oğul, İrem
Abstract: The purpose of the research is to investigate when young children develop brand awareness by means of using some clues. A total of 66 children, aged 3–5, attending a preschool participated in the research. Individual interviews were performed to investigate children's brand awareness. In line with this purpose, the brand logo, brand character and 41 flashcards containing some photos belonging to the product packaging of the brand were presented to the children. The children were instructed to say the name of the brand and the product it belonged to after looking at the photos on the cards. The results of this research showed brand awareness in children as early as 3 years old. Even 3‐year‐old children remembered both the brand and the product after seeing the brand's logo, packaging and character. The young children, however, had more difficulties in remembering the brand's name, and most of the time, they remembered the product but not the brand's name correctly. While the age of the children was an important predictor of brand awareness, the effect of gender was not significant. There were differences in the variety of brands that were remembered by the female and male children. Brand awareness showed an increase in direct proportion to age.